2016
DOI: 10.5603/fm.a2016.0002
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial cells of Cajal — systematic review

Abstract: This paper reviews the distribution of interstitial cells of Cajal (ICC) (Folia Morphol 2016, 75, 3: 281-286)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 66 publications
0
39
0
2
Order By: Relevance
“…ICCs exist in the digestive tract, including in the esophagus, stomach, proximal duodenum wall, small and large bowel, ileum, appendix, and colon [6]. ICCs function as smooth muscle pacemaker cells in the digestive tract where they promote gastrointestinal electrical activity.…”
Section: Introductionmentioning
confidence: 99%
“…ICCs exist in the digestive tract, including in the esophagus, stomach, proximal duodenum wall, small and large bowel, ileum, appendix, and colon [6]. ICCs function as smooth muscle pacemaker cells in the digestive tract where they promote gastrointestinal electrical activity.…”
Section: Introductionmentioning
confidence: 99%
“…There is proof that the nerves in different layers of the GI wall undergo DAN changes and that the parasympathetic fibers in the gut are disrupted in DM patients[114]. Furthermore, ICCs are pacemaker cells in the GI tract distributed along the GI wall[120]. In GI tract, ICCs play an important role for the link between the autonomic nervous system, enteric neurons and smooth muscle cells[121].…”
Section: Diabetes-induced Sensory-motor Changes In the Intestine And mentioning
confidence: 99%
“…It is well known that long-term hyperglycemia can induce the formation and accumulation of AGEs which play an important role for DAN[68-70]. ICC, together ENS and smooth muscles, play an important role in the regulation of motility[120]. One study demonstrated that a high dietary saturated fat intake is associated with significant increase in the prevalence of constipation in patients with uncontrolled DM[167].…”
Section: Clinical Consequences Of Diabetes-induced Changes In Intestimentioning
confidence: 99%
“…Po svojim patohistološkim karakteristikama nalikuje drugim tumorima iz skupine mezenhimalnih tumora (lejomiom, lejomiosarkom, švanom, sinovijalni sarkom) pa je imunohistokemija neophodna za postavljanje dijagnoze 6 . GIST kao mezenhimalni tumor nastaje iz intersticijskih Cajalovih stanica 4,5,7 . Te su intersticijske stanice međusobno umrežene i umetnute između stanica glatkog mišićja GIT-a s kojima tvore dodir na mjesta slična sinapsama.…”
Section: Uvodunclassified